Conversation of the Molecular Structure of Yeast Phenylalanine Transfer RNA in Two Crystal Forms - Klug, A. (1974)
A comparison is made between the electron density maps of the monoclinic and orthorhombic crystal forms of yeast tRNA(Phe) which have been obtained respectively by ourselves and by another group. It is concluded that the molecular structures are essentially the same in both crystals, although the models derived from the maps are not the same. The relation between the two molecular packings is discussed, and it is suggested that the intermolecular contact in the orthorhombic form which is not present in the monoclinic form, may arise through base pairing of the anticodons of neighboring molecules.